A Comparative Analysis of Pharmacological and Non-Pharmacological Treatments for Perinatal Depression - Apanowicz, Lena; Mazur, Joanna; Bułka, Zofia; Michalik, Zuzanna; Kapelka, Klaudia; Malik, Stanisław; Paduch , Przemysław; Kłos, Dawid; Leja, Duszan; Czech, Klaudia; Zdrojewska , Kaja; Gogól-Fijał, Klaudia; et al. (Journal of Education, Health and Sport, 2026)
Introduction: Perinatal depression is one of the most common mental health disorders occurring during pregnancy and the postpartum period. It negatively affects maternal well-being, infant development, and overall family functioning. Due to limitations associated with pharmacotherapy during this sensitive period, as well as increasing interest in safer, non-pharmacological approaches, growing attention is being paid to the role of lifestyle factors in both prevention and treatment. Aim: The aim of this study was to review current evidence regarding the impact of selected lifestyle factors, including dietary supplementation and physical activity, as well as pharmacotherapy, on the risk and severity of perinatal depression. The study also evaluates their role as supportive therapeutic elements. Materials and Methods: A literature review was conducted using PubMed, SCOPUS, Web of Science, and ScienceDirect, including studies published up to January 2026. Randomized controlled trials, meta-analyses, and review articles were included, focusing on supplementation and physical activity. Results: Evidence suggests that vitamin D, iron, zinc, and probiotics may reduce depressive symptoms. Physical activity shows moderate benefits. SSRIs have limited effectiveness, while neurosteroids and ketamine are under investigation. Conclusion: Lifestyle factors may support treatment, but further research is needed. A combined therapeutic approach appears most effective.